Power converter systems for wind generation - Shantha Dharmasiri Gamini Jayasinghe (2013)
Wind energy conversion is the fastest growing renewable energy technology with an exponential growth in the worldwide installed capacity. Since the extraction of maximum possible power from the wind is extremely important for the better utilization of wind energy conversion systems (WECSs), almost all the modern wind turbines operate in the variable speed mode. Permanent magnet synchronous generators (PMSGs) are becoming popular as the most efficient generator for such systems. However, PMSGs require full-scale back-to-back connected power electronic converter systems to decouple generator dynamics from the grid. Conventional two-level converter systems do not meet voltage and power requirements of modern multi-mega-watt WECSs. Therefore, this research was focused on studying suitable multi-level converter topologies for such systems. Furthermore, energy storage is becoming essential in wind energy conversion systems for mitigating power fluctuations. The popular energy storage elements such as batteries and supercapacitors need interfacing converters which introduce additional power losses and cost. Direct integration of energy storage elements into the back-to-back converter has been identified in this research as a potential solution to eliminate these additional power losses and cost. Therefore, battery and/or supercapacitor direct integration capabilities of popular multi-level converter topologies are investigated. Furthermore, an analysis on reactive power injection capability of individual wind turbine generator systems and the need of a centralized reactive power compensator are also presented in this thesis followed by the proposal of a novel static synchronous compensator (STATCOM).